Social environment and its influence on processes of technological modernization (Путеводитель предпринимателя, 2020)
In article questions of the social environment as peculiar mechanism of reproduction and depreciation of the human capital which admits the civilized world part of national wealth and the most important factor of economic growth, innovations and technological modernization are considered.